Interactions between lipoproteins and the arterial wall - Habenicht, Andreas; Salbach, Peter; Janssen-Timmen, Uwe (Principles and treatment of lipoprotein disorders, 1994)
Epidemiological evidence indicates that hypercholesterolemia, smoking, diabetes mellitus, and hypertension are major “risk factors” for cardiovascular disease. However, until now the molecular mechanisms of how these and other risks trigger the disease have escaped detection (Scrott et al. 1972; Goldstein and Brown 1977, 1989; Havel and Kane 1989; Steinberg et al. 1989; Hauss 1990; Brown and Goldstein 1986, 1990; Schwartz et al. 1991; Cambien et al. 1992). Furthermore, unlike cancerogenesis with the discovery of oncogenes and tumor suppressor genes, no unifying hypothesis of atherogenesis has emerged (Bishop 1987; Henderson et al. 1991; Weinberg 1985, 1991). This lack of direction is not surprising, because atherosclerosis is a chronic, multicellular, and probably multistep disease that manifests itself in several distinguishable morphological forms as well as in different parts of the arterial tree depending on the risk factor (Ross and Glomset 1974a,b; Ross 1986). Nevertheless, significant progress has recently been made in our understanding of arterial wall biology. These results have shed new light on the potential molecular origins of the disease and in particular on mechanisms that are associated with hypercholesterolemia. In this chapter we will focus on the relation between atherogenesis and hypercholesterolemia.
Gesehen am 22.05.2025